2021
DOI: 10.1093/ehjdh/ztab074
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ preferences regarding the digital capturing of patient-reported outcomes: planning the future follow-up in a prospective heart failure registry

Abstract: Background Digital health technologies have the potential to improve patient care sustainably. A digital capturing of patient-reported outcome measures (PROM) could facilitate patients’ surveillance and endpoint assessment within clinical trials especially in heart failure (HF) patients. However, data regarding the availability of digital infrastructure and patients’ willingness to use digital health solutions are scarce. Therefore, we conducted a survey as part of a digital-based HF registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The Helios Health Institute constitutes a research institution adjacent to Helios Health GmbH, a large European health care provider, which includes the Helios hospital network consisting of 89 acute care hospitals in Germany. As has been shown previously [ 3 , 13 ], there is considerable restraint among patients with CVD to use health-related mobile technology. Therefore, the initial evaluation of user or patient satisfaction and engagement in the specific tool is a crucial part of implementing novel mHealth solutions.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…The Helios Health Institute constitutes a research institution adjacent to Helios Health GmbH, a large European health care provider, which includes the Helios hospital network consisting of 89 acute care hospitals in Germany. As has been shown previously [ 3 , 13 ], there is considerable restraint among patients with CVD to use health-related mobile technology. Therefore, the initial evaluation of user or patient satisfaction and engagement in the specific tool is a crucial part of implementing novel mHealth solutions.…”
Section: Methodsmentioning
confidence: 71%
“…Despite the multiple advantages and possibilities of mHealth, some obstacles in implementation could arise with respect to the digital capabilities of distinct patient cohorts. A survey conducted recently in a cohort of patients with HF showed that less than half were interested in a digital solution for PROM capturing in the context of an HF registry and many participants preferred a web-based solution over an app-based solution [ 13 ]. Possible differences in digital capabilities may apply to patients with AF, as first TeleCheck-AF results showed good acceptance of the digital solution in an AF cohort with a median age of 64 years [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application and benefits have been thoroughly studied among patients with cardiovascular diseases (CVDs) [2,3], which led to comprehensive position papers focusing on mHealth implementation in subspecialties of cardiovascular (CV) medicine, such as cardiac arrhythmia management [4,5] and CV prevention [6,7]. Patients with heart failure (HF) [8] and coronary artery disease [9,10] may also benefit from mHealth interventions; however, further research is needed as study results are in part inconsistent [11,12], and limitations with respect to patients' digital capabilities exist [13]. Moreover, mHealth technologies are not yet implemented routinely in CVD patient care, mostly due to the lack of solid data [14].…”
Section: Overviewmentioning
confidence: 99%